The Impact of Using a Blend of Plyometric Training "Depth Jump to Rimp Jump and Box Jump" on Jump Shooting - Muhammad Agusman; Muh Usbah; Moh. Ifkhal Sianto; Ardiansyah D. Kandupi; Sardiman Sardiman (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The primary aim of this study is to conduct an in-depth analysis of the effects of the plyometric combination training method, specifically "depth jump to rim jump and box jump," on the jump shooting performance of basketball players. The study aims to investigate the diverse impacts and variations this training method may have on the overall jump-shooting outcomes of the basketball players involved. Materials and methods. In this study, an experimental approach utilizing a 2 x 2 factorial design is being implemented. The study comprises 20 participants who are basketball players from Tadulako University. The data analysis for this study is being conducted using the SPSS 20.0 software. Result. The results of the research showed that the success of jump shots was noticeably influenced by a specific plyometric combination training approach, particularly the incorporation of “depth jump to rim jump" and "box jump" techniques”. Conclusion. Based on the investigation findings, implementing a plyometric combination training program that includes depth jumps, rim jumps, and box jumps can enhance jump shooting performance for basketball players at Tadulako University.